Health Protocol Sanctions Policy in Sorong Mayor Regulation - Sakti Ramdhon Syah Rakia, Alwiyah (Amsir Law Journal, 2021)
This study aims to analyze the policy of legal sanctions of public health protocols in Article 7 of Sorong Mayor Regulation Number 17 of 2020. This study uses normative research that is qualitatively analyzed. This research uses a legal approach. The results of this study show that sanctions in the form of monetary fines as stipulated in Article 7 paragraph (2) letter a have no firm legal basis and tend to potentially interfere with economic activities to improve the welfare of the people, especially in the era of the covid-19 pandemic.